OpenCV 4 Computer Vision Application Programming Cookbook : Build complex computer vision applications with OpenCV and C++, 4th Edition /: Build complex computer vision applications with OpenCV and C++, 4th Edition. (2019) - Millán Escrivá, David; Laganiere, Robert
No abstract available